A comparison of the nutritive value of azolla (Azolla pinnata var. imbricata and duckweed (Lemna perpusilla) for Nile tilapia (Oreochromis niloticus L.) - Castanares, Ma. Alma G.; Edwards, Peter; Yakupitiyage, Amararatne; Little, David C.; British Government (Bangkok : Asian Institute of Technology, 1990)
Feeding a nd digestibility experiments were conducted to compare the nutritive values of azolla (Azolla pinnata var. imbricata) and duckweed ( Lemna perpusilla.} for sex-reversed Nile tilapia ( Oreochromis niloticus L. ). The 70 days feeding experiment was conducted in outdoor concrete tanks with recirculating and static water systems. The fish (average weight of 23.5g stocked at 5.6 fish/m3) were fed ad libitum with fresh Azolla and Lemna, a nd with commercial herbivore pellet s. Based on nutrient composition, digestibility, feed utilization and fish growth, Lemna was nutritionally better than Azolla and was comparable to pellet. Apparent dry matter digestibility (%) of Lemna and Azolla were 60.08 and 48.55 for small fish and 32. 95 and 24.86 for big fish, respectively, whereas the apparent protein digestibility (%} was 96.18 and 62.06 for s mall fish and 92.29 and 38.52 for big fish, respectively. The corresponding f eeding rates (feed dry matter, % body weight/day) were 6.63 and 3.55 for Lemna and Azolla in recirculating water, and 3. 70 a nd 3.06 in static water, respectively. Feed conversion ratios for Lemna and Azolla (dry matter basis) were 2.23 and 3.17 in clear water (equivalent to 30.50 and 47.10 on wet feed basis) and 1.99 a n d 2.76 in static water (equivalent to 27 .17 and 40.90 on wet feed basis} , respectively. The fish utilized protein in Lemna more efficiently than in Azolla. Fish fed Lemna with a mean crude protein content of 31.11% , P:E ratio of 25.14mg/kJ and gross energy of 14.87kJ/g, had a relative growth rate (RGR, g/g/day} , daily weight gain (DWG, g/day) and mean final weight (MFW, g) of 0.08 , 1.76 and 144. 77, respectively in recirculating water tanks; while fish fed Azolla containing 22.06% crude protein, 17.44mg /kJ protein-energy (P:E) ratio and 14.62kJ/g gross energy, h a d RGR, DWG and MFW of 0.02, 0.37 and 49.67, respectively. In the static water system, growth of the Azolla-fed fish (RGR=0.02, DWG=0.37 , MFW=48.83} was similar to the Azolla-fed fish in the recirculating water system, w hereas Lemna-fed fish in the static water system h a d significantly poorer growth (RGR=0.04, DWG=0.90, MFW=88.0} than Lemna-fed fish in t he recirculating water system although they gained more weight than Azolla-fed fish.
A thesis submitted in partial fulfillment requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1990
Keywords: Tilapia; Fishes -- Feeding and feeds